Experimental and numerical investigation of stiffened composite curved panel under shear and in-plane bending. (March 2016) - Ge, Dongyun; Mo, Yuming; He, Boling; Wu, Yiting; Du, Xuzhen
Abstract: An experiment was carried out to study the buckling and post-buckling behavior of stiffened composite curved panel under shear and in-plane bending. A test fixture was designed uniquely which was suitable for curved panel subjected to shear or shear and in-plane bending. The results showed that this kind of fixture was feasible. The strain data were recorded by strain gauges. The out-of-plane displacement field was characterized by a 3D digital speckle system. The stability of stiffened composite curved panel subjected to shear and in-plane bending was analyzed by the obtained data. Finite element method (FEM) was used. The influence of transverse frames on the stability of stiffened curved panel was further studied by FEM. Good correlation between experimental and FEM analysis was obtained. The fixture and test method used in this paper provide a reference to the study of curved panel subjected to shear or shear and in-plane bending.